Virtual education as a training strategy in students - Elizabeth Solórzano Zambrano, Mónica; Carmita Zambrano Montes, Lubis (International Journal of Psychosocial Rehabilitation, 2020)
Education as a strategy Training consists of including in teaching processes, innovation methodologies that allow the development of access routes to education in different social environments. The present study detailed the virtual teaching methodologies or modalities applied in the training process of the students, using bibliographic and deductive-inductive research as a method of data collection. Allowing the acquisition of new knowledge through innovative themes that guarantee the quality of virtual programs, such as the incorporation of information and communication technologies. The function of each of the training-didactic principles implemented in a virtual learning environment was detailed, as well as the types and tools of each of the resources associated with these environments and the types of activities that can be used with their respective advantages for use in such virtual environments. The evaluation of a virtual learning environment is necessary to verify if the knowledge imparted is being adequately captured by the students, for this reason the types of evaluation applied in the virtual training processes were detailed.